PRECLINICAL STUDENTS’ PERCEPTION TOWARDS FACTORS OF ACHIEVING MEDICAL COMPETENCE - Christine Tjahjadinata; Natalia Puspadewi; Elisabeth Rukmini (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Based on the existing research, medical competence achievements in DKI Jakarta’s primary health care was lower than other provinces in Indonesia. Some of the competence achievements in preclinical years were also lower than the level of competence achievement in the Standard of Indonesian Doctor Competence, regardless the diseases are at the third and fourth levels. This research aimed at exploring the factors which influenced the competence achievement of the preclinical years based on student’s perceptions.Methods: The research was a descriptive analytic study with a qualitative approach using Focus Group Disscussion (FGD). Nine preclinical students of 2013 batch were chosen purposefully based on the recommendation from faculty members and students. Data were analyzed qualitatively using thematic analysis method.Results: There are several factors that influence the competence achievement of the preclinical students. These included the factors of student, curriculum, faculty, environmental, and facility. There were four participants in the first meeting and five participants in the second meeting.Conclusion: Based on student’s perception, the factors which affect the competence achievements in preclinical years are student factors, curriculum factors, faculty factors, environmental factors, and facility factors. Keywords: competence, medical education, preclinical, qualitative